2003
DOI: 10.2337/diabetes.52.9.2227
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Insulin Analog With Unique Properties

Abstract: The potentially enhanced mitogenic activity of insulin analogs represents a safety risk that requires detailed analysis of new analogs considered for therapeutic applications. We assessed the signaling properties and mitogenic potency of two novel rapid-acting insulin analogs, Lys Insulin therapy of diabetic patients aims to achieve tight blood glucose control to reduce the progression of long-term complications (1). However, the pharmacokinetic characteristics of currently available insulin preparations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 48 publications
3
37
2
Order By: Relevance
“…In rat cardiomyocytes, a prominent phosphorylation of IRS-2 has been described, with only marginal IRS-1 phosphorylation (7). Comparable results were obtained for human skeletal muscle cells incubated with an extensive amount of insulin glulisine (7). Moreover, an inhibition of cytokine and fatty acidϪinduced apoptosis was described in a rat insulinoma cell line through activation of IRS-2 and was favored as an antiapoptotic activity of insulin glulisine, thereby opening a new field for optimized insulin treatment (10).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In rat cardiomyocytes, a prominent phosphorylation of IRS-2 has been described, with only marginal IRS-1 phosphorylation (7). Comparable results were obtained for human skeletal muscle cells incubated with an extensive amount of insulin glulisine (7). Moreover, an inhibition of cytokine and fatty acidϪinduced apoptosis was described in a rat insulinoma cell line through activation of IRS-2 and was favored as an antiapoptotic activity of insulin glulisine, thereby opening a new field for optimized insulin treatment (10).…”
Section: Discussionmentioning
confidence: 49%
“…Recent studies have revealed that insulin glulisine predominantly activates the IRS-2Ϫdependent pathway (7,10). Because enhanced IRS-2 signaling has been proposed to be involved in mitogenic signal transduction, the phosphorylation state of IRS-2 was determined in vivo in lysates of muscle and liver after insulin stimulation.…”
Section: Autophosphorylation Of the Insulin Receptor After Stimulatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions the affinity of a certain insulin analogue towards IGF-1R becomes increasingly important. It has been shown that AspB10 and glargine have a six to eightfold and insulin lispro a 1.5-fold higher affinity for IGF-1R than normal insulin [21], while aspart [31] and glulisine [32,33] have a low affinity for IGF-1R, like normal insulin.…”
Section: Discussionmentioning
confidence: 99%
“…A reasonable mechanism for the decreased mitogenic activity of HMR1964 was recently suggested by Rakatzi et al [18], who demonstrated in an in vitro model that HMR1964 shows lower IRS-1 phosphorylation than regular insulin.…”
Section: Discussionmentioning
confidence: 99%